A Case of Atrial Tachycardia Circulating around a Left Atrial Roof Scar with Diabetes Mellitus and Renal Failure on Hemodialysis. (11th April 2016) - Hijioka, Naoko; Kamioka, Masashi; Suzuki, Hitoshi; Takeishi, Yasuchika
Abstract : Introduction . Little is known about the effects of volume change by hemodialysis (HD) and mechanical stress caused by an anatomical structure being in contact with the left atrium on the progression of atrial remodeling. We experienced a case of atrial tachycardia (AT) in a patient who had left atrial (LA) scarring at the LA roof and a low-voltage area with slow conduction around the LA scar as components of AT circuit. Here, we present the conceivable hypothesis of the LA scar and the low-voltage area formation. Our concept can be useful in developing a strategy for ablation in a patient with chronic renal failure (CRF) on HD. Case Report . A 65-year-old man with CRF on HD was referred for AT ablation. Three-dimensional electroanatomical mapping revealed that the AT conducted around an LA scar in a counterclockwise fashion. There was a slow conduction area at the superior side of the LA scar, where the AT was terminated during the ablation. Computed tomography indicated a close relationship between the LA and the anatomical structures (ascending aorta and pulmonary artery). Conclusion . Volume change by HD and close contact of anatomical structures to the LA can promote atrial remodeling, resulting in AT occurrence.